2022
DOI: 10.21037/qims-21-786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI features about two types of silent cerebral small-vessel disease in type-2 diabetes mellitus: a retrospective cross-sectional study in a tertiary hospital

Abstract: Background: The present study aimed to evaluate the frequency of silent cerebral small-vessel disease, especially lacunes and white matter hyperintensities, in patients with or without the impaired glucose tolerance (IGT) and type-2 diabetes mellitus, and to characterize the diabetes-correlated factors related to silent cerebral small-vessel disease.Methods: This is a retrospective cross-sectional study. Totally 698 patients were included in this study, from January 2014 to December 2019, among which 270 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…To date, the results of studies investigating the relationship between HbA1c levels and cerebral SVD have been inconsistent. [9][10][11][12][13][14][15] In this study, although higher HbA1c levels showed higher odds of higher cerebral SVD scores, this relationship was not significant.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…To date, the results of studies investigating the relationship between HbA1c levels and cerebral SVD have been inconsistent. [9][10][11][12][13][14][15] In this study, although higher HbA1c levels showed higher odds of higher cerebral SVD scores, this relationship was not significant.…”
Section: Discussioncontrasting
confidence: 68%
“…A few previous studies showed that a higher glycated haemoglobin (HbA1c) level is associated with a higher burden of WMH, 9 cerebral microbleeds, 10 and incident lacunes, 11 whereas many studies did not show significant associations. [12][13][14][15] Some studies have reported that metrics of glycaemic variability, which cannot be gleaned from the evaluation of HbA1c alone, were associated with a higher volume of WMH. 16,17 Continuous glucose monitoring (CGM) has become more common in managing people with diabetes in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type-2 diabetes mellitus (T2DM) is a well-established risk factor for cerebrovascular diseases, such as ischemic stroke [ 3 , 4 ]. Recent studies have suggested that T2DM is one of the major risk factor for microangiopathy and that patients with diabetes mellitus are more likely to suffer from CSVD [ 5 , 6 ]. A comprehensive review revealed a substantial correlation between an elevated risk of small subcortical infarcts or white matter hyperintensity (WMH) and prediabetes and increased glycated hemoglobin A1c (HbA1c) level [ 7 ].…”
Section: Introductionmentioning
confidence: 99%